2017
DOI: 10.1007/s11999-016-5059-x
|View full text |Cite|
|
Sign up to set email alerts
|

Osteochondritis Dissecans Lesions in Family Members: Does a Positive Family History Impact Phenotypic Potency?

Abstract: Background Although repetitive microtrauma and athletic overuse patterns are most commonly associated with osteochondritis dissecans (OCD), recent studies have identified a potential genetic predisposition for OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Despite the growing interest in osteochondritis dissecans lesions of the knee(4, 9, 2527), there is no consensus on incidence of these lesions or the rate of surgical management over time with relation to demographic variables such as age and gender. (1, 2, 5) This population-based study describes the incidence of knee OCD lesions and reports on age- and gender- based trends in incidence in the general population over more than three decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing interest in osteochondritis dissecans lesions of the knee(4, 9, 2527), there is no consensus on incidence of these lesions or the rate of surgical management over time with relation to demographic variables such as age and gender. (1, 2, 5) This population-based study describes the incidence of knee OCD lesions and reports on age- and gender- based trends in incidence in the general population over more than three decades.…”
Section: Discussionmentioning
confidence: 99%
“…28, 29 (33, 34) Both increased activity in males combined with the possibility of increased traumatic events can result in repetitive loading and micro-trauma, which have been shown to be a risk factor for OCD lesions. (5, 6, 8, 9) Lastly, emerging studies have revealed genetics to be an important component and may also contribute to the increased risk in males compared to females. (8, 35, 36)…”
Section: Discussionmentioning
confidence: 99%
“…The levels of evidence of the included studies included: 39 case reports, 31 case series, 11 laboratory studies and 5 comparative studies. Among the included studies, 40 articles proposed a biological hypothesis, 9-47 including genetic causes ( n = 27), ossification center deficit ( n = 12), and endocrine disorders ( n = 9). Conversely, 52 articles supported a mechanical hypothesis, 12,13,17,29,34,35,47…”
Section: Resultsmentioning
confidence: 99%
“…An increased incidence of JOCD in monozygotic twins suggests a genetic aetiology to JOCD. 2,31,32 In a recent study, 6 the proportion of patients with a positive family history of OCD was 14%. Other researchers have described familial cases of OCD lesions associated with short stature and multiple lesion sites.…”
Section: Aetiologymentioning
confidence: 96%